Integrated Formation Evaluation Study in Cliff Head Field, Northern Perth Basin, Western Australia - Elkhateeb, Abdelrahman Aly Ahmed (Curtin University, 2021)
A new technique was implemented to unlock the reservoir characterisation in complex reservoirs. Integration between the conventional density log and the NMR free fluid index has been carried out, through which a high-resolution electrofacies have been classified using a new technique, named the Equivalent Flow Zone Indicator (EFZI). Further, the permeability and water saturation were calculated through new workflows, both are EFZI dependent, with which a high-resolution parameterisation could be achieved for highly complicated reservoirs.